Pharmacokinetics of acetaminophen after a single Oral administration of 20 or 40 mg/kg to 7–9 Day-old foals - Gold, Jenifer R.; Grubb, Tamara; Court, Michael H.; Villarino, Nicolas F. (Frontiers in Veterinary Science, 2023)
Abstract Background: Acetaminophen is utilized in human infants for pain management and fever. Neonatal foals might benefit from administration of acetaminophen but effective and safe dosage regimens for neonatal foals remains to be determined. Objective: The objective was to determine the plasma pharmacokinetics of acetaminophen following oral administration of a single dose of 20 mg/kg or 40 mg/kg to neonatal foals. A secondary objective was to evaluate any changes in hematology and biochemistry profiles. Study Design Randomized study. Methods: Eight clinically healthy 7–9-day old Quarter Horse foals (3 colts and 5 fillies) received a single oral dose of acetaminophen either 20 (n=4) or 40 (n=4) mg/kg. Hematology and biochemistry profiles were evaluated before and seven days after drug administration. Blood samples were collected before and 8 times after acetaminophen administration for 48 hours to quantify plasma acetaminophen concentrations. Plasma pharmacokinetic parameters were estimated using non- compartmental analysis. Results: The median peak plasma concentrations (and range) occurred at 1.5 (0.5-2) hours, and 1.0 (1-2) hours for the 20 and 40 mg/kg doses. The maximum plasma concentration (and range) was 12 (7.9-17.4) µg/ml for the 20 mg/kg dose and 14 (11-18) µg/ml for 40 mg/kg dose. The median AUC0-∞ ranged from 46 to 100 and 79 to 160 h*-µg/mL for the 20 and 40 mg/kg dose respectively. Hematology and biochemistry profiles remained within normal limits. Conclusion: Plasma disposition of acetaminophen after oral administration of 20 and 40 mg/kg to neonates is comparable to adult horses. However, safety and the optimal dosage regimen of acetaminophen for treating pain and or pyrexia in neonates in this age group remains to be determined.